Assessing Translation Quality of Polemical Texts - Abdel Hady, Ahmad S. (2015)
A Master of Arts thesis in Translation and Interpreting MATI (English/Arabic/English) by Ahmad S. Abdel Hady entitled, "Assessing Translation Quality of Polemical Texts," submitted in May 2015. Thesis advisor is Dr. Ahmed Ali. Soft and hard copy available.